Analysis of the Purpose of Use of Funds on the Performance of Companies Conducting Initial Public Offerings (IPO) in 2016-2020 - Mesy Ayusari; Fajri Adrianto; Mohamad Fany Alfarisi (Enrichment : Journal of Management, 2022)
One of the objectives of a company conducting an IPO is to obtain long-term funding and short-term funding without being burdened by interest. As mentioned earlier, the company was founded for the company's sustainability in the long term related to capital such as acquisitions, investments, paying debts, expanding, and many others. Not only in the initial release of shares to the capital market, the ease of obtaining capital will also apply in the future. Several things can be done by companies after carrying out an IPO such as private placement, secondary offering, or through a limited public offering. The first hypothesis found that fixed asset investment partially has a significant effect on profitability. The second hypothesis found that working capital financing has a significant effect on profitability in IPO companies for the 2016-2020 period. The results of testing the third hypothesis found that investment in share of stock partially has a significant effect on profitability. The results of testing the fourth hypothesis found that dept repayment partially has no significant effect on profitability. And the results of testing the fifth hypothesis found that leverage has no significant effect on profitability